PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN EFIKASI DIRI TERHADAP MOTIVASI BELAJAR MELALUI KETERLIBATAN BELAJAR SISWA SMK SWASTA TAMAN SISWA KOTA PEMATANGSIANTAR - Tio Magdalena Sarumpaet, Juliarta; Ruslan, Dede; Zainal, Andri; Thohiri, Roza; Gary Ganda Tua Sibarani, Choms (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of learning motivation among Grade XI Accounting students at SMK Swasta Taman Siswa Pematangsiantar, as indicated by the lack of student participation in learning activities, low responsibility in completing assignments, and insufficient mastery of learning materials. These conditions are presumed to be influenced by the inadequate utilization of information technology, low levels of students’ self-efficacy, and insufficient student engagement in the learning process. This study aims to analyze the effect of information technology utilization and self-efficacy on learning motivation, both directly and indirectly through student engagement as a mediating variable. This study employs a quantitative approach with descriptive and verificative methods. The population consists of all Grade XI Accounting students at SMK Swasta Taman Siswa Pematangsiantar, totaling 70 students, with total sampling technique applied. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that information technology utilization and self-efficacy have a positive and significant effect on both learning motivation and student engagement. Student engagement also has a positive and significant effect on learning motivation and is proven to mediate the relationship between information technology utilization and self-efficacy on learning motivation. Simultaneously, these variables contribute significantly to improving students’ learning motivation. The findings suggest that improving learning motivation is not only influenced by external factors such as technology but also by internal factors such as self-efficacy and active student engagement in the learning process. Therefore, efforts are needed to enhance the utilization of information technology, improve students’ self-efficacy, and encourage student engagement to achieve better learning motivation.